A PBT / PC plastic alloy material and preparation method thereof
By using grafting technology and coating technology in PBT/PC plastic alloy materials, the compatibility and adhesion of materials are improved, and the problems of insufficient strength and toughness of existing materials are solved, thereby achieving higher mechanical properties and wider application prospects.
Patent Information
- Application Number
- CN202410950741.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-07-16
AI Technical Summary
Existing PBT/PC plastic alloy materials have poor performance in strength and toughness, limiting their application range.
Maleic anhydride grafted with methyl acrylate-butadiene-styrene terpolymer, nanotalc powder grafted with glycidyl methacrylate after chitosan coating, anhydrous sodium phosphate and antioxidants were mixed with PBT and PC, and the compatibility and adhesion of the material were improved through grafting technology and coating technology.
It significantly improves the strength, toughness and processing fluidity of PBT/PC plastic alloy materials, and broadens its application areas.
Smart Images

Figure BDA0004947163750000092 
Figure BDA0004947163750000093 
Figure BDA0004947163750000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of plastic polymer materials, and more specifically, to a PBT / PC plastic alloy material and a preparation method thereof. Background Art
[0002] PBT (polybutylene terephthalate) and PC (polycarbonate) are engineering plastics that are widely used in today's society. As one of the semi-crystalline aromatic polyesters, PBT has excellent processing fluidity, thermal stability, wear resistance, solvent resistance and other characteristics, but due to its poor notch sensitivity, it is often limited when used as a structural load-bearing member in engineering plastics. PC, as a non-crystalline engineering plastic, has strong notch load-bearing capacity, thermal stability, and excellent insulation properties, but the cost is relatively high. Therefore, in current industrial production applications, considering the performance and cost of the materials, the two are often prepared into new alloy materials to complement each other, and then modified, such as adding toughening agents, glass fibers, inorganic fillers and other additives, to finally develop high-performance, low-cost alloy plastics, which are widely used in 3D printing consumables, new energy, automotive parts, electronic devices, optical fiber cable casings and other fields.
[0003] In the preparation of PBT / PC plastic alloy materials, when PBT and PC are melt-extruded by twin screws, the non-crystalline part of PBT can have good compatibility with PC, but due to the fast crystallization rate of PBT, the compatible part with PC is small, and PBT / PC materials with good performance cannot be obtained after blending. Although the comprehensive performance of PBT / PC plastic alloy materials has been significantly improved by adding toughening agents, glass fibers, inorganic fillers and other additives, its strength and toughness still cannot reach a high level, which greatly limits the application scope of PBT / PC plastic alloy materials. Summary of the invention
[0004] In order to solve the above technical problems, the present application provides a PBT / PC plastic alloy material and a preparation method thereof. The PBT / PC plastic alloy material not only has excellent strength, but also has extremely strong toughness and has a relatively broad application prospect.
[0005] In the first aspect, the present application provides a PBT / PC plastic alloy material, which adopts the following technical solution:
[0006] A PBT / PC plastic alloy material comprises, by weight, 20-60 parts of PBT, 30-70 parts of PC, 2-15 parts of terpolymer of methyl acrylate-butadiene-styrene grafted with maleic anhydride, 3-5 parts of nano talc powder grafted with glycidyl methacrylate after being coated with chitosan, 0.1-1.0 parts of anhydrous sodium phosphate and 0.5-1.0 parts of an antioxidant.
[0007] Specifically, the terpolymer of methyl acrylate-butadiene-styrene grafted with maleic anhydride is prepared by the following method:
[0008] An initiator, maleic anhydride and a terpolymer of methyl acrylate-butadiene-styrene in a weight ratio of 1:1:(64-65) are melt-blended, extruded and granulated, and then dried to obtain a terpolymer of methyl acrylate-butadiene-styrene grafted with maleic anhydride.
[0009] Wherein, the initiator is dodecyl mercaptan. It is also within the scope of the present application that the skilled person in the art can use other initiators with similar properties commonly used in the art according to actual conditions.
[0010] Specifically, the nano talc powder coated with chitosan and grafted with glycidyl methacrylate is prepared by the following method:
[0011] S1, adding nano talc and chitosan in a weight ratio of (1.8-2.2):1 into water and performing ultrasonic dispersion, and then stirring and reacting at room temperature for 2.0-2.5 hours, and then centrifuging, filtering, washing, and drying to obtain chitosan-coated nano talc;
[0012] S2. Mix glycidyl methacrylate and water in a volume ratio of 1:(1.8-2.2) to obtain a mixed solution, and add chitosan-coated nano talc and an initiator to the mixed solution, wherein the mass volume ratio of the chitosan-coated nano talc to the mixed solution is 0.3g / mL-0.4g / mL, and the mass volume ratio of the initiator to the mixed solution is 0.006g / mL-0.007g / mL. After ultrasonic dispersion, the mixture is stirred and reacted at a temperature of 95°C-105°C for 5.0-5.5 hours, and then centrifuged, washed, dried, and ground to obtain nano talc coated with chitosan and grafted with glycidyl methacrylate.
[0013] Wherein, in step S2, the initiator is sodium dodecyl sulfate. It is also within the scope of the present application that the skilled person in the art can use other initiators with similar properties commonly used in the art according to actual conditions.
[0014] By adopting the above technical scheme, the present application adopts a terpolymer of methyl acrylate-butadiene-styrene grafted with maleic anhydride (abbreviated as MBS-g-MAH), nano talc powder grafted with glycidyl methacrylate after being coated with chitosan (abbreviated as TP-CS-GMA), anhydrous sodium phosphate (abbreviated as AMSP), and an antioxidant mixed with PBT and PC, giving full play to the synergistic effect of each component, so that the prepared PBT / PC plastic alloy material has excellent strength and toughness, as well as good processing fluidity.
[0015] Specifically, compared with simply using a core-shell type terpolymer of methyl acrylate-butadiene-styrene (MBS for short) as a compatibilizer and impact modifier, the present application introduces cyclic anhydride type maleic anhydride (MAH for short) into the MBS molecular chain through a grafting technique, which can not only utilize MAH to have a toughening effect on PC, but also use it as a reactive segment to produce a chemical reaction with PBT, so that PC and PBT are very firmly bonded together, greatly improving the toughness and strength of the PBT / PC plastic alloy material, and broadening the application field of the PBT / PC plastic alloy material.
[0016] At the same time, the present application uses TP-CS-GMA to replace the nano talc powder (referred to as TP) used in the prior art, and can use chitosan (referred to as CS) coated on the surface of TP with good biocompatibility and interface compatibility to reduce the interaction between TP and the plastic substrate. At the same time, the glycidyl methacrylate (referred to as GMA) grafted on TP is used as a reactive epoxy group to change the surface properties of TP and improve the adhesion between TP and the matrix material, and jointly enhance the interface compatibility and bonding force between TP and the matrix material, thereby significantly improving the reinforcing effect of TP on the PBT / PC plastic alloy material and improving the fluidity of the melt, thereby further improving the mechanical properties of the PBT / PC plastic alloy material. In addition, CS is first coated on the surface of TP and then grafted with GMA, which can effectively improve the grafting rate of GMA on the surface of TP. In addition, the presence of CS can also reduce the possibility of TP being eroded by the external environment, thereby improving the stability of TP in the PBT / PC plastic alloy material.
[0017] In addition to the above, the AMSP of the present application, as an ester exchange inhibitor, effectively controls the degree of ester exchange reaction between PBT and PC during melt blending or injection molding, and further improves the toughness, strength and stability of the PBT / PC plastic alloy material.
[0018] Preferably, in step S1, the nano talc is first subjected to the following treatment before being added to water:
[0019] Nano talc powder, ethanol, water, silane coupling agent and oxalic acid in a weight ratio of (4-6):(55-65):(25-35):(2.5-3.5):1 are mixed and ultrasonically dispersed, and then stirred and reacted at a temperature of 55°C-65°C for 2.0-2.5 hours, and then filtered, washed and dried to obtain surface-modified nano talc powder.
[0020] The silane coupling agent is γ-(methacryloyloxy)propyltrimethoxysilane, model KH570. Other silane coupling agents with similar properties commonly used in the art according to actual conditions are also within the scope of the present application.
[0021] Through the above technical solution, the present application uses a silane coupling agent to perform surface modification on TP, which can reduce the interaction between TPs, thereby improving its dispersibility in the matrix material, and further improving the reinforcing effect of TP in the PBT / PC plastic alloy material.
[0022] In the present application, the ultrasonic dispersion time is within the range of 10-30 minutes; the centrifugation is performed by a centrifuge; the filtration is performed by a vacuum filter; the washing is performed by ethanol washing and filtration for 3-4 times; the drying is performed in an oven at 50°C-60°C for 12 hours. Those skilled in the art can make routine adjustments within a reasonable range based on experience, which is also within the scope of the present application.
[0023] Optionally, the antioxidant includes a phenolic antioxidant and / or a phosphite antioxidant.
[0024] In this application, the phosphite antioxidant, antioxidant 168, is taken as an example for description.
[0025] In the second aspect, the present application provides a method for preparing a PBT / PC plastic alloy material, which adopts the following technical solution:
[0026] A method for preparing a PBT / PC plastic alloy material comprises the following steps:
[0027] PBT, PC, terpolymer of methyl acrylate-butadiene-styrene grafted with maleic anhydride, nano talc coated with chitosan and grafted with glycidyl methacrylate, anhydrous sodium phosphate and an antioxidant are mixed evenly, then melt-blended and extruded at a temperature of 220° C.-270° C., and then pelletized and dried to obtain a PBT / PC plastic alloy material.
[0028] In summary, this application has the following beneficial technical effects:
[0029] (1) The PBT / PC plastic alloy material of the present application not only has excellent strength, but also has extremely strong toughness and stability, and can be widely used in various occasions, with extremely broad application prospects;
[0030] (2) The present application uses MBS-g-MAH instead of traditional MBS, which effectively improves the compatibility between PBT and PC, thereby improving the toughness and strength of the PBT / PC plastic alloy material;
[0031] (3) The present application adopts TP-CS-GMA instead of traditional TP, which significantly improves the dispersibility of TP in the matrix material, enhances the interface compatibility and bonding force between TP and the matrix material, thereby significantly improving the reinforcing effect of TP on PBT / PC plastic alloy materials and improving the fluidity of the melt;
[0032] (4) The present application effectively controls the degree of transesterification reaction between PBT and PC during melt blending or injection molding by adding a certain amount of AMSP as an ester exchange inhibitor, thereby further improving the toughness, strength and stability of the PBT / PC plastic alloy material. DETAILED DESCRIPTION
[0033] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0034] Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically:
[0035] PBT, purchased from DuPont, USA, brand name PBT SK605;
[0036] PC, purchased from Dongguan Lerui Plastic Co., Ltd., model number NRVW4526;
[0037] MBS, purchased from Mitsubishi Chemical, Japan, brand SX-006;
[0038] MAH, purchased from Jiangsu Leien Environmental Protection Technology Co., Ltd.;
[0039] Dodecyl mercaptan, tert-dodecyl mercaptan, purchased from Jinan Century Tongda Chemical Co., Ltd.;
[0040] TP, purchased from Lingshou County Jiaao Mineral Products Co., Ltd., nanometer grade;
[0041] Chitosan was purchased from Huantai County Jinhu Crust Products Co., Ltd.;
[0042] Glycidyl methacrylate was purchased from Jinan Kaichuang Chemical Co., Ltd.;
[0043] Sodium dodecyl sulfate was purchased from Hubei Weishi Chemical Reagent Co., Ltd.;
[0044] Silane coupling agent KH570, purchased from Shandong Yunxin New Materials Technology Co., Ltd.;
[0045] Antioxidant 168 was purchased from Nanjing Milan Chemical Co., Ltd.
[0046] Preparation Example 1
[0047] MBS-g-MAH was prepared by the following method:
[0048] 1.5 kg of dodecyl mercaptan and 1.5 kg of MAH were mixed and stirred evenly, fed evenly from the side feeding port of the twin-screw, melt-blended with 96 kg of MBS through a twin-screw extruder, granulated, and dried in an oven at 50° C. for 12 hours to obtain MBS-g-MAH.
[0049] Preparation Example 2
[0050] MBS-g-MAH was prepared by the following method:
[0051] 1.5 kg of dodecyl mercaptan and 1.5 kg of MAH were mixed and stirred evenly, fed evenly from the side feeding port of the twin-screw, melt-blended with 97.5 kg of MBS through a twin-screw extruder, granulated, and dried in an oven at 60° C. for 12 hours to obtain MBS-g-MAH.
[0052] Preparation Example 3
[0053] TP-CS-GMA was prepared by the following method:
[0054] S1. Disperse 90 kg of TP and 50 kg of CS in 1000 L of deionized water, perform ultrasonic dispersion for 10 minutes, and then stir and react at room temperature for 2.0 hours. Centrifuge, filter with a vacuum filter, wash and filter with ethanol for 3 times, and dry in an oven at 50°C for 12 hours to obtain TP-CS.
[0055] S2. 50 L of GMA and 90 L of water were mixed to obtain a mixed solution, and 42 kg of TP-CS and 0.84 kg of sodium dodecyl sulfate were added to the mixed solution. After ultrasonic dispersion for 30 minutes, the mixture was stirred and reacted at 95° C. for 5.5 hours, and then centrifuged and washed repeatedly with ethanol for 4 times, dried in an oven at 60° C. for 12 hours, and ground to obtain TP-CS-GMA.
[0056] Preparation Example 4
[0057] TP-CS-GMA was prepared by the following method:
[0058] S1. Disperse 110 kg of TP and 50 kg of CS in 1000 L of deionized water, perform ultrasonic dispersion for 15 minutes, and then stir and react at room temperature for 2.5 hours. Centrifuge, filter with a vacuum filter, wash and filter with ethanol repeatedly for 4 times, and dry in an oven at 55°C for 12 hours to obtain TP-CS.
[0059] S2. 50 L of GMA and 110 L of water were mixed to obtain a mixed solution, and 64 kg of TP-CS and 1.12 kg of sodium dodecyl sulfate were added to the mixed solution. After ultrasonic dispersion for 30 minutes, the mixture was stirred and reacted at a temperature of 105° C. for 5 hours, and then centrifuged and washed repeatedly with ethanol for 3 times, dried in an oven at 50° C. for 12 hours, and ground to obtain TP-CS-GMA.
[0060] Preparation Example 5
[0061] TP-CS-GMA was prepared by the following method:
[0062] S1. Disperse 100 kg of TP and 50 kg of CS in 1000 L of deionized water, perform ultrasonic dispersion for 10 minutes, and then stir and react at room temperature for 2 hours. Centrifuge, filter with a vacuum filter, wash and filter with ethanol repeatedly for 4 times, and dry in an oven at 50°C for 12 hours to obtain TP-CS.
[0063] S2. 50 L of GMA and 100 L of water were mixed to obtain a mixed solution, and 50 kg of TP-CS and 1 kg of sodium dodecyl sulfate were added to the mixed solution. After ultrasonic dispersion for 30 minutes, the mixture was stirred and reacted at a temperature of 100° C. for 5 hours, and then centrifuged and washed repeatedly with ethanol for 3 times, dried in an oven at 50° C. for 12 hours, and ground to obtain TP-CS-GMA.
[0064] Preparation Example 6
[0065] The difference from Preparation Example 5 is that: before step S1, TP is also subjected to surface modification treatment, and the rest is the same as Preparation Example 5. The surface modification treatment is specifically:
[0066] 120 kg of TP, 1950 kg of ethanol, 750 kg of water, 105 kg of silane coupling agent KH570 and 30 kg of oxalic acid were mixed and ultrasonically dispersed for 10 minutes, then stirred and reacted at a temperature of 55°C for 2.5 hours, then filtered through a vacuum filter, and repeatedly washed and filtered with ethanol for 3 times, and dried in an oven at 50°C for 12 hours to obtain surface-modified TP.
[0067] Preparation Example 7
[0068] The difference from Preparation Example 5 is that: before step S1, TP is also subjected to surface modification treatment, and the rest is the same as Preparation Example 5. The surface modification treatment is specifically:
[0069] 120 kg of TP, 1100 kg of ethanol, 700 kg of water, 50 kg of silane coupling agent KH570 and 20 kg of oxalic acid were mixed and ultrasonically dispersed for 10 minutes, then stirred and reacted at 65°C for 2 hours, then filtered through a vacuum filter, washed and filtered repeatedly with ethanol for 4 times, and dried in an oven at 60°C for 12 hours to obtain surface-modified TP.
[0070] Preparation Example 8
[0071] The difference from Preparation Example 5 is that: before step S1, TP is also subjected to surface modification treatment, and the rest is the same as Preparation Example 5. The surface modification treatment is specifically:
[0072] 120 kg of TP, 1440 kg of ethanol, 720 kg of water, 72 kg of silane coupling agent KH570 and 24 kg of oxalic acid were mixed and ultrasonically dispersed for 10 minutes, then stirred and reacted at 60°C for 2 hours, then filtered through a vacuum filter, repeatedly washed and filtered with ethanol for 3 times, and dried in an oven at 50°C for 12 hours to obtain surface-modified TP.
[0073] Comparative Preparation Example 1
[0074] The difference from Preparation Example 5 is that step S2 is removed and TP-CS is prepared using the same method as step S1.
[0075] Comparative Preparation Example 2
[0076] The difference from Preparation Example 5 is that step S1 is removed, TP is used instead of TP-CS in step S2, and the rest is prepared by the same method as step S2 to obtain TP-GMA.
[0077] Example 1
[0078] A method for preparing a PBT / PC plastic alloy material comprises the following steps:
[0079] 20 kg of PBT, 70 kg of PC, 7.4 kg of MBS-g-MAH prepared in Preparation Example 1, 2 kg of TP-CS-GMA prepared in Preparation Example 3, 0.1 kg of AMSP and 0.5 kg of antioxidant 168 were mixed evenly, then melt-blended and extruded at a temperature of 220° C., and then pelletized and dried in an oven at 50° C. for 12 hours to obtain a PBT / PC plastic alloy material.
[0080] Example 2
[0081] A method for preparing a PBT / PC plastic alloy material comprises the following steps:
[0082] 30 kg of PBT, 51 kg of PC, 3 kg of MBS-g-MAH prepared in Preparation Example 2, 5 kg of TP-CS-GMA prepared in Preparation Example 4, 0.2 kg of AMSP and 0.8 kg of antioxidant 168 were mixed evenly, then melt-blended and extruded at a temperature of 270° C., and then pelletized and dried in an oven at 50° C. for 12 hours to obtain a PBT / PC plastic alloy material.
[0083] Example 3
[0084] A method for preparing a PBT / PC plastic alloy material comprises the following steps:
[0085] 45 kg of PBT, 45 kg of PC, 6 kg of MBS-g-MAH prepared in Preparation Example 1, 3 kg of TP-CS-GMA prepared in Preparation Example 5, 0.5 kg of AMSP and 0.5 kg of antioxidant 168 were mixed evenly, then melt-blended and extruded at a temperature of 240° C., and then pelletized and dried in an oven at 50° C. for 12 hours to obtain a PBT / PC plastic alloy material.
[0086] Example 4
[0087] A method for preparing a PBT / PC plastic alloy material comprises the following steps:
[0088] 50 kg of PBT, 35 kg of PC, 11 kg of MBS-g-MAH prepared in Preparation Example 2, 3 kg of TP-CS-GMA prepared in Preparation Example 3, 0.5 kg of AMSP and 0.5 kg of antioxidant 168 were mixed evenly, then melt-blended and extruded at a temperature of 250° C., and then pelletized and dried in an oven at 50° C. for 12 hours to obtain a PBT / PC plastic alloy material.
[0089] Example 5
[0090] A method for preparing a PBT / PC plastic alloy material comprises the following steps:
[0091] 60 kg of PBT, 30 kg of PC, 15 kg of MBS-g-MAH prepared in Preparation Example 1, 3 kg of TP-CS-GMA prepared in Preparation Example 5, 1 kg of AMSP and 1 kg of antioxidant 168 were mixed evenly, then melt-blended and extruded at a temperature of 260° C., and then pelletized and dried in an oven at 50° C. for 12 hours to obtain a PBT / PC plastic alloy material.
[0092] Example 6
[0093] A method for preparing a PBT / PC plastic alloy material, which is different from Example 3 in that TP-CS-GMA prepared in Preparation Example 6 is used instead of TP-CS-GMA prepared in Preparation Example 5, and the rest is the same as Example 3.
[0094] Example 7
[0095] A method for preparing a PBT / PC plastic alloy material, which is different from Example 3 in that TP-CS-GMA prepared in Preparation Example 7 is used instead of TP-CS-GMA prepared in Preparation Example 5, and the rest is the same as Example 3.
[0096] Example 8
[0097] A method for preparing a PBT / PC plastic alloy material, which is different from Example 3 in that TP-CS-GMA prepared in Preparation Example 8 is used instead of TP-CS-GMA prepared in Preparation Example 5, and the rest is the same as Example 3.
[0098] Comparative Example 1
[0099] The difference from Example 3 is that MBS is used instead of the MBS-g-MAH prepared in Preparation Example 1, and the rest is the same as Example 3.
[0100] Comparative Example 2
[0101] The difference from Example 3 is that TP is used instead of TP-CS-GMA prepared in Preparation Example 5, and the rest is the same as Example 3.
[0102] Comparative Example 3
[0103] The difference from Example 3 is that TP-CS prepared in Comparative Preparation Example 1 is used instead of TP-CS-GMA prepared in Preparation Example 5, and the rest is the same as Example 3.
[0104] Comparative Example 4
[0105] The difference from Example 3 is that TP-GMA prepared in Comparative Preparation Example 2 is used instead of TP-CS-GMA prepared in Preparation Example 5, and the rest is the same as Example 3.
[0106] Comparative Example 5
[0107] The difference from Example 3 is that PBT is 10 kg, PC is 80 kg, MBS-g-MAH is 0.5 kg, TP-CS-GMA is 8 kg, antioxidant 168 is 1.5 kg, and the rest is the same as Example 3.
[0108] Comparative Example 6
[0109] The difference from Example 3 is that PBT is 85 kg, PC is 2 kg, MBS-g-MAH is 25 kg, TP-CS-GMA is 0.2 kg, AMSP is 2 kg, antioxidant 168 is 0.2 kg, and the rest is the same as Example 3.
[0110] Performance Testing
[0111] The above Examples 1-8 and Comparative Examples 1-6 were subjected to melt flow rate test, tensile strength test, elongation test, Izod notched impact strength test, flexural strength test, flexural modulus test, density test, and thermal shrinkage test, and the test standards are as follows:
[0112] (1) The tensile strength test and elongation test shall be carried out in accordance with the method specified in GB / T 1040.1-2006;
[0113] (2) The Izod notched impact strength test shall be carried out in accordance with the method specified in GB / T 1843-2008;
[0114] (3) The melt flow rate test shall be carried out in accordance with the method specified in GB / T 3682-2000. Before the test, the sample shall be dried at 110℃±1 for 4h.
[0115] (4) The flexural strength test and flexural modulus test shall be carried out in accordance with the method specified in GB / T 9341, and the test speed shall be (2.0±0.4) mm / min;
[0116] (5) Density test shall be carried out according to the immersion method specified in GB / T 1003.1-2008;
[0117] (6) Heat shrinkage rate: the raw material is injection molded into a 80mm×10mm×4mm sample, and the sample length L0 is tested with a vernier caliper. Then the sample is placed in a talcum powder bath that has been preheated to 100℃±1℃, and can be freely hung on the sample rack without affecting the free expansion and contraction of the sample. After 4 hours, the sample is taken out, cooled to room temperature, and the sample length L1 is tested. The heat shrinkage rate is calculated according to formula ①, and the arithmetic average of the experimental results of 5 samples is taken as the test result.
[0118] The above performance test results are shown in Table 1.
[0119] Table 1 Performance test results
[0120]
[0121] Table 1
[0122]
[0123]
[0124] Data Analysis:
[0125] As can be seen from Table 1, the tensile strength of the PBT / PC plastic alloy material prepared in Examples 1-5 of the present application is 56MPa-63MPa, the elongation is 132%-288%, the melt flow rate is 7.8-12.0, and the Izod notched impact strength at 23°C is 87KJ / m 2 -94KJ / m 2 , -30℃ Izod notch impact strength is 35KJ / m 2 -65KJ / m 2 , flexural strength is 71MPa-84MPa, flexural modulus is 1943MPa-2345MPa, density is 1.22g / cm 3 -1.27g / cm 3 , the heat shrinkage rate is 0.05%-0.15%. The test data show that the PBT / PC plastic alloy material prepared in Examples 1-5 of the present application not only has excellent strength and thermal stability, but also reaches a super-tough state at room temperature of 23°C, and still has high toughness at a low temperature of -30°C, and can be widely used in various occasions, with extremely broad application prospects.
[0126] The difference between Example 6-8 and Example 3 is that the TP in the TP-CS-GMA used is surface-treated with a silane coupling agent before coating CS. It can be seen from Table 1 that the mechanical properties and thermal stability of Examples 6-8 are stronger than those of Example 3, which indicates that surface modification of TP in advance can reduce the interaction between TPs, thereby improving its dispersibility in the matrix material, and further improving the reinforcing effect of TP in the PBT / PC plastic alloy material.
[0127] The difference between Comparative Example 1 and Example 3 is that ordinary MBS is used instead of the MBS-g-MAH of the present application. It can be seen from Table 1 that although the strength of Comparative Example 1 is similar to that of Example 3, the elongation of Example 3 is significantly higher than that of Comparative Example 1. Since the strength and elongation are inversely proportional, when the elongation of Comparative Example 1 is much lower than that of the present application, the strength is not much higher than that of Example 1. Combined with other data in Table 1, it can be fully explained that the present application uses MBS-g-MAH instead of MBS, which can significantly improve the compatibility and toughness of the alloy material, and make the material super tough while ensuring the strength.
[0128] The difference between Comparative Example 2 and Example 3 is that ordinary TP is used instead of TP-CS-GMA of the present application. It can be seen from Table 1 that although the strength of Comparative Example 2 is similar to that of Example 3, the elongation of Example 3 is significantly higher than that of Comparative Example 2. Since the strength and elongation are inversely proportional, when the elongation of Comparative Example 2 is much lower than that of the present application, the strength is not much higher than that of Example 1. Combined with other data in Table 1, it can be fully explained that the present application uses TP-CS-GMA instead of TP, which can significantly improve the reinforcing effect of TP on the PBT / PC plastic alloy material and improve the fluidity of the melt, thereby further improving the mechanical properties and thermal stability of the PBT / PC plastic alloy material.
[0129] The difference between Comparative Example 3 and Example 3 is that TP-CS is used instead of TP-CS-GMA of the present application. It can be seen from Table 1 that although the strength of Comparative Example 3 is similar to that of Example 3, the elongation of Example 3 is significantly higher than that of Comparative Example 3. Since the strength is inversely proportional to the elongation, when the elongation of Comparative Example 3 is much lower than that of the present application, the strength is not much higher than that of Example 3. Combined with other data in Table 1, it can be fully explained that the present application further grafts GMA on TP-CS, which can change the surface properties of TP, and together with CS, it plays a role in improving the interface compatibility and bonding force between TP and the matrix material, thereby improving the reinforcing effect of TP on the PBT / PC plastic alloy material and improving the fluidity of the melt, thereby further improving the mechanical properties and thermal stability of the PBT / PC plastic alloy material.
[0130] The difference between Comparative Example 4 and Example 3 is that Comparative Example 4 directly grafts GMA on the surface of TP. It can be seen from Table 1 that although the strength of Comparative Example 4 is similar to that of Example 3, the elongation of Example 3 is significantly higher than that of Comparative Example 4. Since the strength is inversely proportional to the elongation, when the elongation of Comparative Example 4 is much lower than that of the present application, the strength is not much higher than that of Example 3. Combined with other data in Table 1, it can be fully explained that the present application first coats CS on TP and then grafts GMA, which can further increase the grafting rate of GMA on the TP surface, thereby further improving the reinforcement effect of TP on the alloy material.
[0131] The difference between Comparative Examples 5-6 and Example 3 is that the dosage ratio of each raw material of the alloy material is not within the scope of the present application. It can be seen from Table 1 that when the dosage ratio of each raw material is not within the scope of the present application, the mechanical properties and thermal stability of the alloy material will be significantly reduced.
[0132] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A PBT / PC plastic alloy material, characterized in that: By weight, the raw materials include 20-60 parts of PBT, 30-70 parts of PC, 3-15 parts of terpolymer of methyl acrylate-butadiene-styrene grafted with maleic anhydride, 2-5 parts of nano talc powder grafted with glycidyl methacrylate after being coated with chitosan, 0.1-1.0 parts of AMSP and 0.5-1.0 parts of antioxidant; The terpolymer of methyl acrylate-butadiene-styrene grafted with maleic anhydride is prepared by the following method: The initiator, maleic anhydride and terpolymer of methyl acrylate-butadiene-styrene in a weight ratio of 1:1:(64-65) are melt-blended and extruded into granules, and then dried to obtain terpolymer of methyl acrylate-butadiene-styrene grafted with maleic anhydride; The nano talc powder coated with chitosan and grafted with glycidyl methacrylate is prepared by the following method: S1. Add nano talc powder and chitosan in a weight ratio of (1.8-2.2):1 into water and perform ultrasonic dispersion, then stir and react at room temperature for 2.0-2.5 hours, then centrifuge, filter, wash and dry to obtain chitosan-coated nano talc powder; S2. Mix glycidyl methacrylate and water in a volume ratio of 1:(1.8-2.2) to obtain a mixed solution, and add chitosan-coated nano talc and an initiator to the mixed solution, wherein the mass volume ratio of the chitosan-coated nano talc to the mixed solution is 0.3g / mL-0.4g / mL, and the mass volume ratio of the initiator to the mixed solution is 0.006g / mL-0.007g / mL. After ultrasonic dispersion, stir the reaction at a temperature of 95°C-105°C for 5.0-5.5 hours, and then centrifuge, wash, dry and grind to obtain nano talc coated with chitosan and grafted with glycidyl methacrylate.
2. A PBT / PC plastic alloy material according to claim 1, characterized in that: In the step S1, the nano talc is first subjected to the following treatments before being added to water: Nano talc powder, ethanol, water, silane coupling agent and oxalic acid in a weight ratio of (4-6): (55-65): (25-35): (2.5-3.5): 1 are mixed and ultrasonically dispersed, and then stirred and reacted at a temperature of 55°C-65°C for 2.0-2.5 hours, and then filtered, washed and dried to obtain surface-modified nano talc powder.
3. A PBT / PC plastic alloy material according to claim 1, characterized in that: The antioxidant includes a phenolic antioxidant and / or a phosphite antioxidant.
4. A method for preparing the PBT / PC plastic alloy material according to claim 1, characterized in that: The following steps are involved: PBT, PC, terpolymer of methyl acrylate-butadiene-styrene grafted with maleic anhydride, nano talc coated with chitosan and grafted with glycidyl methacrylate, AMSP and antioxidant are mixed evenly, then melt-blended and extruded at a temperature of 220° C.-270° C., and then pelletized and dried to obtain a PBT / PC plastic alloy material.
Citation Information
Patent Citations
Graphene reinforced conductive PC / PBT alloy for electronic carrier tape
CN111808412A
High-toughness low-floating-fiber reinforced PC / PBT alloy material and preparation method thereof
CN113462141A
High-toughness heat-resistant flame-retardant PC / PBT alloy material and preparation method thereof
CN115011084A